Pancreatic Cancer Survival Outcomes at a Tertiary Medical Center Based on Sex and Geographic Location. Issue 11 (November 2016) - Sathyamurthy, Anjana; Chela, Harleen; Romana, Bhupinder; Yousef, Mohamad; Winn, Jessica; Madsen, Richard; Bechtold, Matthew; Asombang, Akwi W.
Abstract : Objectives: To describe the survival outcomes of patients with histologically proven primary pancreatic cancer based on geographic location and sex. Methods: We conducted a retrospective review of medical records from 2009 through 2013 of patients with pancreatic cancer using International Classification of Diseases, Ninth Revision code 157.9 and International Statistical Classification of Diseases, 10th Revision code C 25.9. The variables extracted included demographics, date of diagnosis, mode of diagnosis, duration, treatment methods, family history, history of chronic pancreatitis, and diabetes mellitus. ZIP codes were used to identify the geographic location of each subject, and rural urban commuting area codes were used to further classify the areas as metropolitan, micropolitan, small town, and rural. Population sizes were classified as metropolitan >50, 000, micropolitan 10, 000 to 49, 999, small town 2500 to 9999, and rural <2500. Descriptive analysis and Kaplan-Meier survival for survival outcomes were performed with statistical significance identified as P < 0.05. Results: A total of 400 medical charts were extracted for review, 301 of which belonged to patients with primary pancreatic cancer. Of the 301 cases, we identified 175 men (58%), 125 women (41%), and 1 missing sex data. There were 280 whites (95%), 8 African Americans (2%), 2 Asian Americans (0.64%), 1 Hispanic American (0.34%) and 1 Native American (0.34%), with a mean age of 63.2 ± 12.6 years. Based on geography, there were 34%, 27%, 20%, and 19% in rural areas, metropolitans, small towns, and micropolitans, respectively. No statistically significant difference was noted in sex on survival outcomes ( P = 0.85) or geography ( P = 0.62). Additional analysis revealed no statistical significant difference between sexes when stratifying by location ( P = 0.96). Conclusions: There is no difference in survival outcomes of patients with primary pancreatic cancer based on sex or geographic location. Our survival outcomes differ from the national survival outcomes, which reveal that mortality in men is higher than it is in women. Abstract : Trends in survival outcomes of pancreatic cancer have shown a 1-year survival rate from approximately 17% to 28% and 5-year survival remains below 10%. Understanding risk factors is important in treatment and the development of tools to improve patient outcomes.